2017
DOI: 10.1039/c7nj00211d
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable catalytic activity of a sulfonated mesoporous polymer (MP-SO3H) for the synthesis of solketal at room temperature

Abstract: A sulfonic acid-functionalized mesoporous polymer (MP-SO3H) catalyst was prepared via post-synthetic modification of mesoporous polydivinylbenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“… a From BJH method, b taken from reference 53 , c measured by acid–base titration, d av = average pore diameter from BET. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a From BJH method, b taken from reference 53 , c measured by acid–base titration, d av = average pore diameter from BET. …”
Section: Resultsmentioning
confidence: 99%
“…The acidity present in MP-SO 3 H-X and Amberlyst-15 is measured by acid–base titration. The acidity values of sulfated zirconia, and HBEA are taken from the literature (Table S2 ) 53 . The CHNS elemental analysis of the polymeric catalysts has been performed to quantify sulfur content in the catalyst and compared it with the acidity values obtained from titrations.…”
Section: Resultsmentioning
confidence: 99%
“…Note: glycerol to the second reactant ratio was presented as molar ratio. The MP-SO3H catalyst performed better than other conventional solid acid catalysts [46] Glycerol and acetone Zr-TUD-1…”
Section: Glycerol and Acetonementioning
confidence: 92%
“…Numerous references reported that mesoporous silica catalysts have the advantage of high stability in the conversion of glycerol to solketal, resulting in products with a relatively large percentage of conversion (95%) and selectivity to solketal (98%) [37,[42][43][44][45][46]. The mesoporous structure with an activated surface by sulfonic acid might be applied efficiently for the conversion of glycerol to fuel additive [37,43,47].…”
Section: Glycerol-to-solketal Over Mesoporous Silicamentioning
confidence: 99%
“…The pore diameters can be tailored and the organic frameworks can be functionalized through co-polymerization and/or post-synthesis organic reactions. [54][55][56][57][58][59] The hydrophobicity-hydrophilicity in the material can be easily tuned by varying the composition of monomers or by post-synthetic modications. The effect of substrate wettability on catalytic activity is an important aspect that is overlooked for a long time in heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%